Letter: liver transplantation for acute HEV infection in cirrhotic patients in France. Issue 4 (14th July 2017) - Borentain, P.; Colson, P.; Gregoire, E.; Allard, G.; Gerolami, R.
Abstract : Linked Content This article is linked to Borentain and Colson et al paper. To view this article visithttps://doi.org/10.1111/apt.14188 .